2021
DOI: 10.1108/qrom-08-2020-2015
|View full text |Cite
|
Sign up to set email alerts
|

Organizational links and sensemaking in a medical work cooperative system

Abstract: PurposeThe aim of this article was to analyze how the presence of the elements that constitute organizational links are related to sensemaking in a cooperative system of medical work.Design/methodology/approachA content analysis was conducted following interviews with the managers of the cooperative, which is a member of the Brazilian cooperative system and one of the largest in the world. This analysis enabled the systematization of the categories that were identified through the coding of responses, aided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
0
6
0
2
Order By: Relevance
“…The study of Jehanzeb ( 2020), for instance, identified a strong relationship between perceived organizational support, employee development and organizational commitment, evidencing the existence of a moderating effect on the person-organization relationship as employees who learn through investments by the organization became more committed to it. This finding is important for managers' decision making when they seek a balance between individual and organizational interests, defining training policies in keeping with organizational strategies, which contribute to the creation of organizational links (Pellin, Weymer, Dissenha, & Bauer, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The study of Jehanzeb ( 2020), for instance, identified a strong relationship between perceived organizational support, employee development and organizational commitment, evidencing the existence of a moderating effect on the person-organization relationship as employees who learn through investments by the organization became more committed to it. This finding is important for managers' decision making when they seek a balance between individual and organizational interests, defining training policies in keeping with organizational strategies, which contribute to the creation of organizational links (Pellin, Weymer, Dissenha, & Bauer, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…A conceptual aspect that deserves to be highlighted is that the interpretations may offer parameters that allow the identification of individuals with the organizations, generating bonds. In this line of reasoning, Pellin et al (2021) state that the work of Karl Weick (1973) makes basic movements that allow an approximation of the study of sensemaking to the study of bonding by understanding organizations as social collectivities in a constant process of creation, maintenance, and dissolution. Weick (1995) defines organizations through organizing, dealing with the organizational process of continuous action, and engagement activity.…”
Section: Sensemaking and Organizingmentioning
confidence: 99%
“…Thus, the concept of sensemaking is central in the suggested model since organizational analysis is related to the continuity and process movements in which people engage and that are triggered by the behavior and meaning creation by these people, especially in cooperative organizations, as evidenced by Pellin et al (2021). Nonetheless, it is essential to note that this approach is closer to the co-evolutionary framework proposed by Cristofaro (2021), not excluding the original Weickian foundations but broadening the view from an integrated perspective.…”
Section: Sensemaking and Organizingmentioning
confidence: 99%
“…Um aspecto conceitual que merece ser destacado nesse momento é que as interpretações podem oferecer parâmetros que permitem a identificação dos indivíduos com as organizações, gerando vínculos. Nessa linha de raciocínio, Pellin et al (2021) afirmam que a obra de Karl Weick (1973) faz movimentos importantes que permitem uma aproximação do estudo do sensemaking ao estudo do vínculo, ao compreender organizações como coletividades sociais em constante processo de criação, manutenção e dissolução. Weick (1995) define as organizações por meio do termo organizing, trazendo uma preocupação com o processo organizacional de ação contínua, uma atividade na qual as pessoas se engajam.…”
Section: Sensemaking E Organizingunclassified
“…Dessa maneira, o conceito de sensemaking é central no modelo sugerido, uma vez que a análise das organizações está relacionada à continuidade e ao movimento dos processos nos quais as pessoas se engajam e que são desencadeados pelo comportamento e criação de sentido por parte dessas pessoas, especialmente em organizações cooperativas, conforme evidenciado por Pellin et al (2021). É importante ressaltar, entretanto, que essa abordagem se aproxima mais da perspectiva coevolutiva proposta por Cristofaro (2021), não excluindo os fundamentos originais weickianos, mas ampliando o olhar numa perspectiva integrada.…”
Section: Perspectivaunclassified